La distinction reloaded: Returns to education, family background, cultural and social capital in Germany - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
The German educational system finds itself being criticized by the OECD in its Programme for International Student Assessment. Family background would heavily influence children's academic achievements. A child stemming from a high class family has a 3.1 times higher chance to go to secondary school than a child from a working class family, controlling for ability. The chance for taking up university studies is even 7.4 times higher for children from high class families. In search of an explanation for this misery Pierre Bourdieu's and James Coleman's theories about cultural and social capital prove to be valuable. Based on their work this study will investigate returns to education and its interdependence with family background in Germany. Bourdieu basically explains that family background leads to acquire specific levels of manners, attitudes, self assurance etc. which in turn might inuence job status, income e.g. A huge body of literature measuring returns to education all over the world already exists, however, studies for Germany, and in particular studies that focuss on the relation between income, education and social background, are rare. This study appears to be the first one following an interdisciplinary approach, incorporating measures of cultural and social capital along with family background and further variables into a common Mincer wage equation. Taking data from the German SOEP for the years 2001 and 2005 indices measuring cultural and social capital are constructed applying principal component analysis. Education, ability, motivation, cultural and social capital are endogenized and adequate regression techniques are applied. It can be shown that social background determines an individual's amount of education which in turn will inuence income. An individual's amount of education does signi_cantly depend on parents' education, the father being a low-skilled laborer, the amount of cultural and social capital, ability and motivation. Males do get more education than women. Educational policy in Germany should concentrate on enhancing access to education for children from low class families on the one hand, on the other hand the German society should be sensitized to special needs of individuals stemming from low class families as well as to problems that these humans do face.
Keywords: I21; J24; J31; Z13; 330; Returns to Education; Cultural Capital; Social Capital; Inequality; Index Construction; Bildungsertrag; Familiensoziologie; Kultur; Social Capital; Bildungschancen; Schätzung; Deutschland